2020
DOI: 10.3390/insects11100673
|View full text |Cite
|
Sign up to set email alerts
|

Bounds on Absolute Gypsy Moth (Lymantria dispar dispar) (Lepidoptera: Erebidae) Population Density as Derived from Counts in Single Milk Carton Traps

Abstract: Estimates of absolute pest population density are critical to pest management programs but have been difficult to obtain from capture numbers in pheromone-baited monitoring traps. In this paper, we establish a novel predictive relationship for a probability (spTfer(r)) of catching a male located at a distance r from the trap with a plume reach D.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(21 citation statements)
references
References 42 publications
0
21
0
Order By: Relevance
“…We tested this protocol for gypsy moth and estimated spTfer(0) = 0.15 and D50 = 45 ± 5 m. This spTfer(0) is lower than the actual experimental spTfer(0)=0.37 observed in the field (Onufrieva et al 2020).…”
Section: Discussionmentioning
confidence: 71%
See 4 more Smart Citations
“…We tested this protocol for gypsy moth and estimated spTfer(0) = 0.15 and D50 = 45 ± 5 m. This spTfer(0) is lower than the actual experimental spTfer(0)=0.37 observed in the field (Onufrieva et al 2020).…”
Section: Discussionmentioning
confidence: 71%
“…We searched the literature for data on insect catches in traps located at various distances from the insect release points that satisfied the following conditions: (1) converged catch (meaning that the value did not increase substantially with increased trapping time, as defined in (Onufrieva et al, 2020) was reported for at least 4 distances between a trap and a release point, (2) number of insects released at large distance was the same or larger than at short distances, (3) no zero catch data points were reported between non-zero points. This search yielded 9 data sets on brown marmorated stink bug ( Halyomorpha halys ) (Kirkpatrick et al, 2019), codling moth ( Cydia pomonella ) (Adams et al, 2017), European pine sawfly ( Neodiprion sertifer ) (Östrand & Anderbrant, 2003), spotted wing drosophila ( Drosophila suzukii ) (Kirkpatrick et al, 2018), Western corn rootworm ( Diabrotica virgifera ) (Wamsley et al, 2006), Douglas fir beetle ( Dendroctonus pseudotsugae ) (Dodds & Ross, 2002), Southern pine beetle ( Dendroctonus frontalis ) (Turchin & Odendaal, 1996), macro-moths in families Erebidae (Merckx & Slade, 2014) and Sphingidae (Beck & Linsenmair, 2006).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations